Estudio de mercado para ampliar la comercialización de cilindros de 15 kilogramos de gas licuado de petróleo (glp) de uso industrial de la empresa pública de hidrocarburos del Ecuador EP petroecuador en el cantón Shushufindi de la provincia de Sucumbíos para el año 2016 - Ruiz Rivera, Ketty Susana (2017)
The Cushion Shushufindi shows the lack of commercialization of Liquefied Petroleum Gas in cylinders of 15 kg, which causes an increase in the price paid by the customer since there are only two marketers in the market, which is why As a general objective "To develop a market study to expand the commercialization of cylinders of 15 kilograms of Liquefied Petroleum Gas LPG for industrial use of the Public Petroleum Company of Ecuador EP PETROECUADOR in the Shushufindi canton, province of Sucumbíos, for the year 2016 The study used the methods: historical, deductive, inductive, analytical, statistical and bibliographic, while for the collection of information the 238 businesses that use the product were determined as the population under study, and as suppliers to EP Ecuador and Duragas, for this the technique of the survey was applied. In the market study it was determined that of the 238 businesses, 81.09% use cylinders with a capacity of 15 kg, of this figure 37.82% acquires industrial LPG, with a per capita consumption of 127 cylinders per year, obtaining A real demand for consumption of 9,235 cylinders, a figure of which 92.22% is willing to purchase the gas from Petroecuador. Currently in Shushufindi there are 2 industrial gas commercialisers which offer to the market 4,812 cylinders, resulting in an unsatisfied demand of 3,705 cylinders. In the marketing plan, a slogan was established for the product. In addition, 6 advertising strategies were established, which will improve customer service and offer you the opportunity to purchase the product. The budget that requires the proposal is $ 18,930.00 resources that will allow to finance the expansion of commercialization of industrial LPG in the Shushufindi canton. In view of the results obtained, it is recommended to expand the commercialization of LPG for industrial use, since there is an unsatisfied demand that needs to be covered. For this purpose, the entity must allocate the necessary resources for the execution of the proposal, in order to guarantee the Success of the project.